Experimental‐numerical test strategy for evaluation of curing simulation of complex‐shaped composite structures: Experimentell‐numerische Teststrategie zur Evaluierung der Aushärtungssimulation für komplex geformte Faserverbundstrukturen. Issue 11 (17th November 2016) - Gude, M.; Schirner, R.; Müller, M.; Weckend, N.; Andrich, M.; Langkamp, A.
Abstract : Numerical analyses of manufacturing processes become more and more essential, in particular for thick‐walled and complex‐shaped components made of fibre‐reinforced thermosets. One of the main problems is the heat accumulation within those laminates caused by the exothermal reaction while curing the thermoset resin. To enable a precise and efficient prediction of the occurring temperatures within the laminate especially for industrial applications, a reliable and time‐saving numerical analysis of curing processes is desirable. Therefore, a novel experimental‐numerical test strategy for a precise prediction of the curing process is presented including both the analytical and experimental determination of numerous thermal and thermo‐chemical material parameters and models for carbon fibre reinforced thermosets. Numerical validation steps are presented in order to evaluate reliability of experimentally determined material parameters and models. Additionally, the developed finite element model was adopted for the curing simulation of a large complex‐shaped turbine fan blade with a thick‐walled root section. Highlight of this work is the extensive experimental validation of the numerical analysed curing process.